PENERAPAN STRATEGI TANDUR UNTUK MENINGKATKAN KETERAMPILAN PROSES SISWA PADA MATA PELAJARAN FISIKA KELAS X IIS 4 LINTAS MINAT SMAN 12 PEKANBARU - Pratiwi, Anggres Intan Pratiwi Intan; ', M.Rahmad; ', M. Sahal (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The aim of this study was to determine the increase of skills in the physics at X IIS 4 Cross Interests in SMAN 12 Pekanbaru using TANDUR strategy on material Temperature and Heat. The research was held from January through June 2015 with subject research is 39 student ofclass X IIS 4 Cross Interests in SMAN 12 Pekanbaru. The form of the research is pre-experimental with one group pretest-posttest design. The research instrument used in the form of process skill achievement test.The result of process skills that were examined include aspect identifying variables, communicating, predicting, classifying and planning experiments, in this study were obtained gain with high category.Besides, the observation aspects and formulating hypotheses derived average gain. The average score of all indicators in the pretest and posttest obtained 0.73 gain with high category, then derived88.54% percentage of average categoryfor the run strategy it self. Nevertheless the research wasconcluded that the application of TANDUR strategy is able to improve students process skills in the subject of physics at X IIS 4 cross interest in SMAN 12 Pekanbaru. Keywords: learning strategies of TANDUR, process skills, temperature and heat.